Implementasi Digital Marketing Public Relations pada UMKM Beatless Burger - Jasmine Nadira Hadiawan; Tresna Wiwitan (UNISBA Press, 2024)
Abstract. In this increasingly advanced era, business actors who want to start their business do a lot of it using social media with digital marketing adding the concept of public relations in it, where for Beatless Burger it is a Micro, Small and Medium Enterprise, which operates in the culinary sector which is established Since 2020, actors have begun to enter the digital world to expand their business markets. By implementing content marketing and social media marketing in marketing their products on Instagram social media by providing important information for their Pop Up activities. The aim of this research is also to examine analyzing the marketing content production process and social media marketing by analyzing the obstacles andreasons for choosing Instagram. The theory used in preparing this thesis uses social construction theory explained by Peter L Berger and Thomas Luckman. This research uses qualitative methodology with a case study research approach, data collection through participant observation, in- depth interviews.The results of this research are that Beatless Burger successfully implemented Digital Marketing Public Relations onInstagram despite the obstacles and efforts as well as the reasons for choosing the Instagram platform to easily disseminate information. Abstrak. Pada perkembangan zaman yang sudah semakin maju ini pelaku usaha yang akan memulai bisnis nya ini banyak melakukandengan media sosial dengan digital marketing menambahkan konsep public relations di dalamnya yang dimana untuk Beatless Burger merupakan Usaha Mikro Kecil Menengah , yang bergerak di bidang kuliner yang berdiri sejak 2020, pelaku mulai memasuki dunia digital untuk memperluas pasar usahanya Dengan melakukan implementasi konten marketing dan sosial media marketing dalam marketing produknya di media sosial instagram dengan memberikan informasi penting untuk kegiatan Pop Upnya.Tujuan Penelitian ini juga untuk mengkaji menganalisis proses produksi konten marketing dan sosial media marketing dengan menganalisis hambatan dan alasan memilih instagram Teori yang digunakan ini menggunakan teori kontruksi sosial yang dipaparkan oleh Peter L Berger dan Thomas Luckman.Penelitian ini menggunakan metodologi kualitatif dengan pendekatan penelitian studi kasus, pengumpulan data melalui observasi partisipan , wawancara mendalam. Hasil dari penelitian ini Beatless Burger berhasil implementasi Digital Marketing Public Relations di instagram dengan adanya hambatan dan upaya serta alasan pemilihan platform instagram mudah menyebarkan informasi.